Qualitative Analysis of Determinants of MSME Financial Performance through the NVivo Approach: A Study of Business Actors in Indonesia - Muhammad Resky; Irawati Irawati; Abdul Rahman Mus; Hajering Hajering (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the determinants of the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a qualitative approach based on NVivo software. This study used in-depth interviews with MSMEs from various business sectors, which were then analyzed through coding, categorization, and theme development using NVivo. The results indicate that MSME financial performance is influenced by several key factors: financial literacy, access to financing sources, utilization of digital technology, managerial skills, and cash flow management strategies. The analysis also reveals the interrelationships between factors that shape adaptive financial decision-making patterns in the face of market dynamics. Data visualization through features such as word frequency, cluster analysis, and relationship models between themes provides a more comprehensive understanding of the complexity of MSME financial management. This study provides theoretical contributions to the development of qualitative-based financial management studies and practical implications for business actors and policymakers in designing strategies to sustainably improve MSME financial performance. This study aims to analyze the determinants of the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a qualitative approach based on NVivo software. This study used in-depth interviews with MSMEs from various business sectors, which were then analyzed through coding, categorization, and theme development using NVivo. The results indicate that MSME financial performance is influenced by several key factors: financial literacy, access to financing sources, utilization of digital technology, managerial skills, and cash flow management strategies. The analysis also reveals the interrelationships between factors that shape adaptive financial decision-making patterns in the face of market dynamics. Data visualization through features such as word frequency, cluster analysis, and relationship models between themes provides a more comprehensive understanding of the complexity of MSME financial management. This study provides theoretical contributions to the development of qualitative-based financial management studies and practical implications for business actors and policymakers in designing strategies to sustainably improve MSME financial performance.